CSF nonphosphorylated Tau as a biomarker for the discrimination of AD from CJD - Ermann, Natalia (John Wiley and Sons Inc., 2018)

(untitled) (Ann Clin Transl Neurol)
Creutzfeldt–Jakob disease and Alzheimer's disease are characterized by the presence of elevated total‐Tau cerebrospinal fluid concentrations while the presence of hyperphosphorylated Tau forms in the cerebrospinal fluid is rather a hallmark of Alzheimer's disease. Here we aimed to investigate potential contribution of nonphospho‐Tau epitopes (non‐P‐Tau) in the discrimination between both diseases. Non‐P‐Tau cerebrospinal fluid concentration was highly increased in Creutzfeldt–Jakob disease (n = 57, 3683 ± 3599 pg/mL) compared to Alzheimer's disease (n = 41, 148 ± 219 pg/mL) and neurological controls (n = 56, 62 ± 40 pg/mL), and significantly improved the proportion of correctly classified patients (99%) compared to that achieved by total‐Tau (90%), P‐Tau (62%) and 14‐3‐3 (91%).